2019
DOI: 10.3389/fphys.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Grounded Sleeping on Recovery After Intensive Eccentric Muscle Loading

Abstract: Purpose: We set out to investigate the effectiveness of grounded sleeping on the time course of recovery with respect to muscle soreness and athletic performance after intensive eccentric muscle loading.Methods: Twenty-two healthy participants were recruited for this study and randomly assigned to an experimental group (GRD, grounded sleeping, n = 12) or control group (UGD, sham-grounded sleeping, n = 10) to evaluate the effects of 10 days recovery with GRD vs. UGD following a single intensive downhill treadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is now clear that the serum level of CK will increase rapidly and that muscle strength decreases when DOMS occurs because of the damage in the skeletal muscle and the subsequent inflammation after intense exercise (Clarkson and Sayers, 1999;Romagnoli et al, 2015;Muller et al, 2019). The current evidence showed that acupuncture intervention reduced the serum level of CK based on the total effect meta-analysis, as well as the subgroup effect on the time points of 24, 48, and 72 h post exercise-induced DOMS, indicating that acupuncture intervention could improve High quality: Further research is very unlikely to change our confidence in the estimate of effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the serum level of CK will increase rapidly and that muscle strength decreases when DOMS occurs because of the damage in the skeletal muscle and the subsequent inflammation after intense exercise (Clarkson and Sayers, 1999;Romagnoli et al, 2015;Muller et al, 2019). The current evidence showed that acupuncture intervention reduced the serum level of CK based on the total effect meta-analysis, as well as the subgroup effect on the time points of 24, 48, and 72 h post exercise-induced DOMS, indicating that acupuncture intervention could improve High quality: Further research is very unlikely to change our confidence in the estimate of effect.…”
Section: Discussionmentioning
confidence: 99%
“… a Decrease (% from baseline) in isometric maximal voluntary contraction (MVC) torque of knee extensors after downhill running (DR); b increase (% from baseline) in blood (plasma and serum) creatine kinase (CK) concentration after DR; c delayed onset muscle soreness (DOMS) response (0–100 mm evaluated on visual analogue scale) for knee extensors after DR. Based on data from original research articles reporting isometric MVC force/torque decrements ( n = 37; [ 5 , 9 , 10 , 15 , 38 , 43 , 58 87 ]), blood CK elevation ( n = 83; [ 14 , 16 , 38 , 40 42 , 44 , 46 , 50 , 59 62 , 65 67 , 70 , 72 75 , 77 , 80 , 81 , 84 , 85 , 87 90 , 92 , 121 , 134 183 ]) and DOMS ( n = 23; [ 8 , 15 , 38 , 58 , 60 , 66 , 71 , 75 , 84 , 89 , 135 , 151 , 156 , 159 , 171 , 178 , 179 , 182 , 184 188 ]) responses immediately post-, 24 h post-, 48 h post-, 72 h post- and 96 h ...…”
Section: Muscular Alterations Following Downhill Runningmentioning
confidence: 99%
“…Three studies examined the impact of grounding on delayed muscle soreness (DOMS). After unaccustomed or strenuous exercise, muscles felt pain, tenderness, and stiffness for several hours to days and concluded that this technique substantially decreased pain and inflammation [25]- [26].…”
Section: Discussionmentioning
confidence: 99%